Testicular Tissue Banking for Fertility Preservation in Young Boys: Which Patients Should Be Included? - Delgouffe, Emily; Braye, Aude; Goossens, Ellen (Frontiers in Endocrinology, 2022)
Due to the growing number of young patients at risk of germ cell loss, there is a need to preserve spermatogonial stem cells for patients who are not able to bank spermatozoa. Worldwide, more and more clinics are implementing testicular tissue (TT) banking programs, making it a novel, yet indispensable, discipline in the field of fertility preservation. Previously, TT cryopreservation was predominantly offered to young cancer patients before starting gonadotoxic chemo- or radiotherapy. Nowadays, most centers also bank TT from patients with non-malignant conditions who need gonadotoxic conditioning therapy prior to hematopoietic stem cell or bone marrow transplantation. Additionally, some centers include patients who suffer from genetic or developmental disorders associated with prepubertal germ cell loss or patients who already had a previous round of chemo- or radiotherapy. It is important to note that the surgical removal of TT is an invasive procedure of which the long-term effects are still largely unknown. Moreover, TT cryopreservation is still considered an experimental procedure as restoration methods are not yet clinically available. For this reason, TT banking should preferably only be offered to patients who are at significant risk of becoming infertile. In our view, TT cryopreservation is recommended for patients in need of high-risk chemo- and/or radiotherapy to treat (non-)malignant diseases, regardless of previous low-risk treatment. TT retrieval during orchidopexy is also proposed for patients with bilateral cryptorchidism. Since patients with a medium- to low-risk treatment generally maintain their fertility, TT banking is not advised for this group. Also for Klinefelter patients, TT banking is not recommended as TT banking does not give better outcomes than a testicular sperm extraction later in life.